Why don’t academic physicians seek needed professional help for psychological distress? (Swiss Medical Weekly, 2012)
PURPOSE: Suicidal thoughts, burnout and other signs of psychological distress are prevalent among physicians. There are no studies concerning help-seeking for psychological distress among university hospital physicians, who face a particularly challenging, competitive work environment. We compare psychologically-distressed university hospital physicians who have not sought needed help with those who have sought such help. We thereby aim to identify factors that may hinder help-seeking and factors that may trigger seeking help. METHODS: Analysis was performed among university hospital physicians reporting recent suicidal thoughts and/or showing other indications of current psychological ill-health. These distressed physicians were a subgroup (42.7%) from the cross-sectional phase I HOUPE study (Health and Organization among University Hospital Physicians in Europe): 366 from Sweden and 150 from Italy. Having sought professional help for depression or burnout was the outcome variable. Multiple logistic regression was performed with socio-demographic factors as covariates. RESULTS: Altogether 404 (78.3%) of these distressed physicians had never sought professional help for depression/burnout. Physicians who were currently involved in medical research, taking night call, surgical specialists, male, or Italian were least likely to have sought help. Physicians who faced harassment at work or who self-diagnosed and self-treated were more likely to have sought help. CONCLUSION: Very few of these university hospital physicians with signs of psychological distress sought help from a mental-health professional. This has implications for physicians themselves and for patient care, clinical research, and education of future physicians. More study, preferably of interventional design, is warranted concerning help-seeking among these physicians in need.